Use of hyaluronic acid as an alternative for reconstruction of interdental papilla - Corte Sánchez, Daniela; Yáñez Ocampo, Beatriz Raquel; Esquivel Chirino, César Augusto (Facultad de Odontología, 2017)
Introduction: Hialuronic acid (HA) is an essential glucosaminoglycan of the extracellular matrix of all tissues; it is found at an average concentration of 0.02%. A subject weighing 60 kg contains approximately 12 g of HA. The greater concentrations of this acid are found in connective tissue such as the skin, which exhibits up to 56% percent of said acid. HA plays an important role in cell migration, since it is involved in processes of growth, infl ammation and reparation as well as stimulation of different connective tissue cells. Objective: To present a clinical case involving interdental papilla reconstruction with HA infi ltration. Clinical case: 24 year old female who reported being systemically healthy. The patient exhibited loss of interdental papilla in the area of tooth number 11 and 21 caused by presence of gingivitis and poor brushing techniques. The patient was assessed according to Nordland and Tarnow classifi cation in order to ascertain the procedure’s degree of predictability; she was additionally examined according to Cardaropoli classifi cation in order to be able to establish pre- and post-treatment comparisons. The patient exhibited 5 mm of contact point to the bone crest, therefore, HA infi ltration was undertaken into the papilla, every seven days for four weeks. Conclusion: There are very few non-surgical techniques to regenerate interdental papillae, one of them is HA use. Research conducted on this technique is not new, nevertheless, it would be suitable to further it taking into consideration different factors; conducting them in greater-sized populations with subjects of different ethnicities and gender, and using different infi ltration intervals.